From Open Journalism to Closed Data: Data Journalism in Italy. Issue 9 (21st October 2019) - Porlezza, Colin; Splendore, Sergio
Abstract: The study investigates how journalists construct the rise of data journalism discursively within the specific political and economic conditions of Italy, and whether data journalists describe it as able to promote transparency at the level of both journalism and society as a whole. Italy is an interesting case for four different reasons: (1) to date, few analyses have been carried out on Mediterranean countries; (2) the Italian media system and its traditional journalism culture appear to be reluctant to innovate; (3) Italian data journalists are generally freelancers linked to small news agencies rather than established newsrooms; (4) the research reported in this paper was accomplished while the Italian government was approving a Freedom of Information Act. From the end of 2015 to the beginning of 2017, we carried out 15 interviews with data journalists working full-time for both established news organizations and specialized agencies. The findings show that data journalism in Italy is a highly professional sub-field, although journalistic education is not well developed. Data journalism is still largely determined by the availability and accessibility of public datasets. However, data journalists have developed certain strategies with which to generate and collect their own data, for instance collaborations and networks.